Dissecting the relationship between fin-tech indicators, natural resources and green productivity in ASEAN: regarding human development and globalization perspectives - He, Chao; Dai, Wanci; He, Jinquan; Li, Xing; Tu, Yulin (Frontiers in Environmental Science, 2025)
In the pursuit of sustainable development, green productivity has emerged as a crucial concept, bridging the gap between ecological conservation and economic prosperity to foster both environmental protection and human welfare. This research undertakes an in-depth exploration of the intricate associations among natural resource utilization, the forces of globalization, advancements in financial technology (fintech), human development, and green productivity within the ASEAN region during the period from 2000 to 2021. Employing advanced econometric techniques such as the Augmented Mean Group (AMG), Common Correlated Effects Mean Group (CCEMG), Fixed Effects modeling, and the Moments Quantile Regression (MMQR) to dissect panel data, the study aims to decipher the multifaceted impacts of these variables on environmental sustainability. The results reveal that overreliance on natural resources and the process of globalization pose challenges to green production, while economic expansion and human development initiatives act as catalysts for sustainability. The symbiotic relationship between human development and green business practices further accentuates the importance of holistic policy formulation. Notably, the findings highlight that the implementation of stringent environmental regulations and the adoption of sustainable resource management strategies not only enhance green production but also stimulate economic growth without compromising environmental integrity. This study not only enriches the theoretical framework of ecological economics but also uncovers the critical interdependencies of sustainability components within the ASEAN context. By spotlighting the necessity for integrated policies that harmonize economic and environmental objectives, this research offers valuable insights to policymakers striving to achieve sustainable development in the region. Moreover, it emphasizes the urgency of a comprehensive approach to address the sustainability conundrums faced by ASEAN nations, paving the way for future investigations into the complex web of multiple sustainability issues prevalent in developing economies.